Seroprevalence of Toxoplasma gondii in White-Tailed Deer (Odocoileus virginianus) in New York State - Emily D. Ledgerwood; Jason D. Luscier (Pathogens)
The parasitic protozoa, Toxoplasma gondii (T. gondii), is a model organism for one health because of its wide-ranging impacts on humans, wildlife, and domestic animals. Intermediate hosts, including white-tailed deer (Odocoileus virginianus), have been implicated in its maintenance. Prior analysis of Toxoplasma gondii seroprevalence in New York State deer focused on rural areas; however, the high density of domestic cats (Felis catus) in urban areas has been implicated in its spread amongst deer. To address this, the seroprevalence of Toxoplasma gondii was assessed across two suburban and urban areas with known deer overabundance in Onondaga and Suffolk County. Here, domestic cats are the only likely definitive host. Between 2019 and 2023, serum from culled deer was collected, and Toxoplasma gondii seropositivity was determined using the modified agglutination test. Overall seroprevalence was 49.31% (n = 144) but was significantly higher in Onondaga (64%) compared to Suffolk County (36%), despite similarities between these two regions. Deer from Onondaga also had higher antibody titers. These data suggest that although urbanization may be a predictor of Toxoplasma gondii seropositivity in deer, there are additional contributing factors. Overall, this study emphasizes the need for continued surveillance in intermediate hosts and informs public health and wildlife management decisions aimed at limiting the impact of Toxoplasma gondii.